2013
DOI: 10.1371/journal.pone.0059680
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Ethanol Exposure Causes Glucose Intolerance with Increased Hepatic Gluconeogenesis and Histone Deacetylases in Adult Rat Offspring: Reversal by Tauroursodeoxycholic Acid

Abstract: Prenatal ethanol exposure results in increased glucose production in adult rat offspring and this may involve modulation of protein acetylation by cellular stress. We used adult male offspring of dams given ethanol during gestation days 1–7 (early), 8–14 (mid) and 15–21 (late) compared with those from control dams. A group of ethanol offspring was treated with tauroursodeoxycholic acid (TUDCA) for 3 weeks. We determined gluconeogenesis, phosphoenolpyruvate carboxykinase (PEPCK), glucose-6-phosphatase, hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 48 publications
8
47
0
Order By: Relevance
“…; Yao et al . ). Clinical studies have also reported that growth restriction is not a prerequisite for development of metabolic syndrome (Euser et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Yao et al . ). Clinical studies have also reported that growth restriction is not a prerequisite for development of metabolic syndrome (Euser et al .…”
Section: Discussionmentioning
confidence: 97%
“…Key effectors are DNMTs, histone acetyltransferases, and histone deacetylase (HDAC) proteins, respectively. Maternal alcohol consumption (E1‐E7) has previously been linked to increased adult hepatic gluconeogenesis in association with increased class II HDAC protein activity (42). Although we did not observe changes in fetal liver Hdac mRNA expression, we cannot rule out the possibility that protein activity of these chromatin modifiers is altered in our model to impact on chromatin accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether GnRH induced FOXO1 acetylation, which would permit an increase in FOXO1 phosphorylation in the presence of insulin of IGF1 despite blunted AKT activity. Using a 10 nM GnRH time course from 0–6 hours and a FOXO1 acetylation antibody (Santa Cruz sc-49437) (7579) we found that GnRH had no effect on FOXO1 acetylation in LβT2 cells (data not shown).…”
Section: Discussionmentioning
confidence: 95%